2015
DOI: 10.1371/journal.pone.0119474
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Confirmation of Computed Tomography-Based Diagnosis of the Atherosclerosis Discovered in 17th Century Korean Mummy

Abstract: In the present study on a newly discovered 17th century Korean mummy, computed tomography (CT) revealed multiple aortic calcifications within the aortic wall that were indicative of ancient atherosclerosis. The CT-based findings were confirmed by our subsequent post-factum dissection, which exhibited possible signs of the disease including ulcerated plaques, ruptured hemorrhages, and intimal thickening where the necrotic core was covered by the fibrous cap. These findings are strong indicators that the mummy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…2). By anatomical, histological, radiological and molecular investigations, signs of congenital or acquired diseases have been identifi ed [2,3,5,6,9,10,11,13]. Th e above-noted research techniques employed in collaborative research have driven the expansion of our understanding of Joseon societies to an unexpectedly high level.…”
Section: Introductionmentioning
confidence: 99%
“…2). By anatomical, histological, radiological and molecular investigations, signs of congenital or acquired diseases have been identifi ed [2,3,5,6,9,10,11,13]. Th e above-noted research techniques employed in collaborative research have driven the expansion of our understanding of Joseon societies to an unexpectedly high level.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, to assess whether atherosclerosis was a condition dependent on the lifestyle of Egyptian elites or if it was also encountered in ancient populations with different subsistence strategies (Allam et al, 2009(Allam et al, , 2011Thompson et al, 2013). Studies have demonstrated atherosclerosis in other prehistoric and historic mummies, including the chalcolithic Iceman, a mummy from the Joseon dynasty, and a pre-agricultural hunter-gatherer population from the Aleutian Islands (Murphy et al, 2003;Abdelfattah et al, 2013;Kim et al, 2015). While research seems to indicate that atherosclerosis is an inherent component of the aging process , it is undeniable that it some cases, such as the mummies from Vilnius, Lithuania, diet and behavior must have played a role (Piombino-Mascali et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found in paleopathological studies of ancient and medieval mummies. The first finding of atherosclerosis confirmed by morphological evidence was made in Egyptian mummies thousands of years old at the beginning of the 20th century (Kim et al, 2015).…”
Section: Introductionmentioning
confidence: 92%